Kecerdasan Emosional dalam Kepemimpinan Pendidikan - Antonius Remigius Abi (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2019)
Educational leadership that has the criterion of emotional quotient is the leader with the ability to influence the educational community through self-awareness and self-management. This ability helps school leaders to understand the society. In other words, the leader has the social awareness and skill management. It is the skill to interact with the shcool community their wants. In addition, the school leaders are required to be honest to their selves and the whole educational community for their building of self strength, self-conscience, honor, and responsibility to the whole school community. To conclude that the cooperation between leaders and society (social community) the goal of the education will be achieved. Abstrak: Kepemimpinan pendidikan yang memiliki kriteria quatition emosional adalah kepemimpinan dengan kemampuan untuk mempengaruhi komunitas pendidikan melalui kesadaran diri dan manajemen diri. Kemampuan ini membantu para pemimpin sekolah untuk memahami masyarakat. Dengan kata lain, pemimpin memiliki kesadaran sosial dan manajemen keterampilan. Ini adalah keterampilan untuk berinteraksi dengan komunitas shcool yang mereka inginkan. Selain itu, para pemimpin sekolah dituntut untuk jujur pada diri mereka sendiri dan seluruh komunitas pendidikan untuk membangun kekuatan diri, hati nurani, kehormatan, dan tanggung jawab mereka kepada seluruh komunitas sekolah. Untuk menyimpulkan bahwa kerja sama antara para pemimpin dan masyarakat (komunitas sosial) tujuan pendidikan akan tercapai.